Divergences in antihypertensive therapy in special situations in nephrology - Lemos, Marcelo Montebello (2008)
CONTEXT AND OBJECTIVE: The choice of an antihypertensive drug is based on several criteria and specific situations give rise to doubt and controversy. The aim here was to evaluate physicians’ approaches towards treatment with antihypertensive agents in specific situations. DESIGN AND SETTING: Cross-sectional study, at Universidade Federal de São Paulo, São Paulo. METHODS: A questionnaire was applied during a nephrology meeting to evaluate individual approaches towards each hypothetical clinical situation. The questionnaire consisted of five multiple-choice questions (clinical cases) concerning controversial aspects of antihypertensive therapy. RESULTS: A total of 165 questionnaires were analyzed. Most participants were nephrologists (93.2%). There was a preference for angiotensin-converting enzyme (ACE) inhibitors in at least two of the cases. Only 57.2% of the physicians were correct in choosing beta-blockers as the first-line drugs for patients with ischemic coronary disease. Moreover, 66.2% chose ACE inhibitors as the first-line drugs for patients with chronic kidney disease and proteinuria. About 5% of the physicians did not follow the current recommendations for the use of ACE inhibitors in diabetic patients with microalbuminuria. The most controversial question concerned the firstline drug for advanced chronic kidney disease. Most physicians were correct in choosing calcium channel blockers and avoiding ACE inhibitors in renovascular hypertension in the case of a patient with a single functioning kidney. CONCLUSIONS: Most physicians adopted the correct approach, but some had an alternative strategy for the same situations that was not based on evidence.